2004
DOI: 10.1080/09540120410001683358
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing acceptability of voluntary counselling and HIV-testing among pregnant women in Northern Tanzania

Abstract: Guided by the conceptual framework of the Health Belief Model, this study aimed to identify factors associated with pregnant women's expressed willingness to accept voluntary counselling and HIV-testing (VCT). A cross-sectional interview survey of 500 pregnant women, complemented by focus group discussions, was conducted in the Kilimanjaro region of Tanzania. Constructs derived from the Health Belief Model explained 41.7% of women's willingness to accept VCT. Perceived high personal susceptibility to HIV/AIDS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
122
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(139 citation statements)
references
References 21 publications
13
122
2
2
Order By: Relevance
“…The women were not tested for HIV and their actual HIV status was not inquired about. The results concerning previous infant feeding practices and expressed willingness to accept voluntary counselling and HIV testing have been presented elsewhere 12,16 . The structured survey was guided by the conceptual framework of Social Cognitive Theory 17 .…”
Section: Focus Group Discussionmentioning
confidence: 99%
“…The women were not tested for HIV and their actual HIV status was not inquired about. The results concerning previous infant feeding practices and expressed willingness to accept voluntary counselling and HIV testing have been presented elsewhere 12,16 . The structured survey was guided by the conceptual framework of Social Cognitive Theory 17 .…”
Section: Focus Group Discussionmentioning
confidence: 99%
“…23 The risk perception of contracting HIV may either increases or decreases the likelihood of using health care services. 24 An example of this phenomenon could be that, since HIV prevalence is reported to be positively associated with higher socio-economic status and education, 25 individuals with higher educational attainment and those who are wealthier may perceive themselves to be at risk of HIV infection, and therefore have recourse for HIV testing, compared to those who are less well-off. 16 There is also evidence of a positive association between HIV awareness and HIV testing, 14 and awareness and education are highly correlated.…”
Section: Introductionmentioning
confidence: 99%
“…Dube and Nkosi [43] found that half of the women in their study felt 50% of respondents expressed willingness to be tested in a Chinese study by Li et al [36] and in an Ethiopian study by Moges and Amberbir [37] ; in contrast, other studies reported higher willingness to be tested (more than 75% of respondents expressed willingness to be tested) [38][39][40] . Some African studies demonstrated significant gaps between the willingness of pregnant women to receive HIV testing and their actual testing rates, as in studies from Sudan [41] and Tanzania [42] . Similarly, a South African study showed that pregnant women had a good level of knowledge and understanding about HIV testing in pregnancy, and their perceptions of HIV testing were positive, but they were not consistent with their behavior.…”
Section: Fear Of the Test Resultsmentioning
confidence: 99%
“…That is, the women's positive attitudes towards HIV testing were not reflected in their actual behavior [43] . The difference between women's willingness to receive HIV testing and actual testing rates implies that willingness to be tested for HIV during pregnancy is a complex phenomenon influenced by an interplay of factors [42,44] . Based on the classification used by Deblonde et al [45] in their literature review on impediments to HIV testing in Europe, in the present review factors related to the willingness of women to be tested for HIV during pregnancy have been classified as policy-related factors, womanrelated factors, and health care provider-related factors.…”
Section: Fear Of the Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation